Orientation and dispersal of Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae) in response to various semiochemicals - Losey, Stephen M. (Kansas State University, 2015)
The rusty grain beetle, Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae), is a very common worldwide pest of stored grains. The orientation of C. ferrugineus beetles to various semiochemicals was studied in both the laboratory and field. In laboratory experiments glass two-choice pitfall bioassay dishes were used. Mixed-sex populations of beetles responded positively and significantly to cucujolide I and II separately and in combination compared to controls. Bioassays using the two aggregation pheromones of the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae). Dominicalure 1 and 2 together elicited unexpected significant attractive responses by C. ferrugineus as did assays with the synthetic pheromones from other species. Bioassays showed that C. ferrugineus were not attracted to either corn meal or rolled oats, but they were attracted to commercial grain-based lures and also to ethanol, a natural fermentation product from grains. Several bioassays were conducted to test the attractiveness of naturally produced beetle volatiles to C. ferrugineus, but these showed no orientation to volatiles from either the beetles or their food only. Field tests were conducted in Kansas to test attractiveness of the synthetic pheromones cucujolide I and II in lures together with wheat versus wheat only as a control using Lindgren funnel traps. Field tests in 2014 with cucujolide II pheromone lures showed a significant response by feral C. ferrugineus when tested against wheat. Other field tests to examine dispersal of C. ferrugineus relative to grain storages showed that more C. ferrugineus were caught on the western side of grain bins compared to other cardinal directions at two different locations. Results from field and laboratory studies suggest that semiochemical-based tools can be developed to study dispersal behavior in field populations of C. ferrugineus.
Keywords: Orientation; Cryptolestes ferrugineus; Semiochemicals; Dispersal; Entomology (0353)